2011
DOI: 10.1063/1.3589802
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of carbon dioxide condensation in the high pressure flows using the statistical BGK approach

Abstract: In this work, we propose a new heat accommodation model to simulate freely expanding homogeneous condensation flows of gaseous carbon dioxide using a new approach, the statistical Bhatnagar-Gross-Krook method. The motivation for the present work comes from the earlier work of Li et al. [J. Phys. Chem. 114, 5276 (2010)] in which condensation models were proposed and used in the direct simulation Monte Carlo method to simulate the flow of carbon dioxide from supersonic expansions of small nozzles into near-vacuu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…18,19 In particular, 19 it was found that the sticking coefficient for the small polyatomic system of water was invariant for cluster sizes above 10 and for temperatures of the order of 100 K. Once the cluster growth rate is estimated in a cell, the rest of the procedure is straight-forward. For each cluster growth event, a cluster of size j is randomly chosen from the cell and increased in size to j + 1.…”
Section: B Cluster Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 In particular, 19 it was found that the sticking coefficient for the small polyatomic system of water was invariant for cluster sizes above 10 and for temperatures of the order of 100 K. Once the cluster growth rate is estimated in a cell, the rest of the procedure is straight-forward. For each cluster growth event, a cluster of size j is randomly chosen from the cell and increased in size to j + 1.…”
Section: B Cluster Growthmentioning
confidence: 99%
“…Therefore, the postcollisional velocities and temperatures of cluster can be calculated using Eqs. (18) and (19). From the evaporation rate relationship, Eq.…”
Section: B New Weighting Scheme In the Bgk Framework For Condensing mentioning
confidence: 99%
“…As previously stated, most DSMC simulations of axisymmetric flows are at least conducted with radially varying weights [2,8,9] with values that increase with the distance to the centerline. This is performed to increase particle counts close to the centerline while preventing an excessive number of particles in cells further removed from it as their volume scales with y.…”
Section: Accuracy and Efficiencymentioning
confidence: 99%
“…These drawbacks inherent to the DSMC method have led to a number of modifications to the basic DSMC algorithm that are in ubiquitous use today. The first is the use of spatially varying weights, particularly for axisymmetric simulations, such as in (amongst many others) [7,8] where the cell volume scales with the distance to the centerline, that allows enough particles to be present close to the centerline while reducing their number further away from it. The second improvement is the use of a spatially varying time step, and an adaptive procedure to calculate the optimum time step field as in, e.g., [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The BGK model assumes that sufficient collisions have taken place in the flow such that individual collisions do not have to be simulated because the flow relaxes to a known velocity distribution. Kumar et al 11 developed a comprehensive homogeneous condensation model to simulate supersonic expansion of CO 2 from small nozzles into near-vacuum conditions in the context of the BGK approach taking into the account of nucleation, cluster-monomer sticking and non-sticking collisions, cluster evaporation, and cluster-cluster coalescence. A new model was proposed to redistribute the heat released in a BGK or DSMC (for low enough pressures) computational cell due to the exothermic processes of nucleation and cluster growth by monomer addition.…”
Section: Introductionmentioning
confidence: 99%